Turbulence of Extraterritorial Power in Southeast Asia - Arthuur Jeverson Maya; Jason Fernando (Eduvest - Journal of Universal Studies, 2025)
The research reveals that power turbulence in Southeast Asia is caused by the involvement of major states in the region. Such involvement has implications for two levels of analysis, where there is a balance of power of intrusive states and a balance of power of regional states. The anomaly is that regional security is created with a high tendency for conflict and politics. The effort to deconstruct this anomaly uses the governmentality power approach and the genealogy method initiated by Michel Foucault. Philosophical debates arise when disciplining and normalizing the history of power and knowledge of intrusive systems. He confirmed that regional order is related to global power. In this regard, this research is limited to revealing the involvement of countries outside the Southeast Asian region carried out since the pre-colonial era by India and China. There is disciplining and normalizing through the censorship of panopticon governmentality and genealogy of power so that the relations of power and knowledge of intrusive systems carried out by countries outside the region gain population approval as contemporary patterns of power produced throughout history and have implications for power.